Upaya Penanganan Defect dengan Metode DMAIC pada Area Packing di PT. X - Rosalina Rosalina; Jani Rahardjo (Jurnal Titra, 2021)
X company produces furniture products and is included in a large furniture company in Indonesia. The production system adopted is a “make by order” system targeting importer buyers (distribution/overseas large stores). The performance in the packing area for 3 months (January-March) has never reached the expected target and the defect rate is 11%. The research was conducted to help improve performance by looking for suggestions that reduce the defect rate in the packing area by analyzing the highest type of defect (chipping). The cause analysis was traced using the Five Whys Diagram methods, and it was found that there were problems in the work environment and work methods that can still be developed. Improvements were implemented in the form of creating and training work standards regarding treatment actions for products and material handling. The implementation of the proposal has succeeded in reducing the defect rate from 11% to 9.72%.